Founder of Hasidism : a quest for the historical Ba'al Shem Tov - Rosman, Murray Jay (Oxford : The Littman Library of Jewish Civilization, 2014)
"Moshe Rosman supplies the history that proves that the Ba'al Shem Tov, the legendary founder of hasidism, actually existed. He presents the best, most convincing description that can be drawn from the existing documentary evidence, changing our understanding of the Besht and altering the master narrative of hasidism. A substantial new Introduction considers what has changed in the study of hasidism since the influential first edition was published. The Ba'al Shem Tov is an elusive subject for historians because documentary evidence about his life is scanty and equivocal. Until now, much of what was known about him was based on stories compiled more than a generation after his death, many of which serve more to mythologize him than to describe him. The portrait Moshe Rosman provides is drawn from life instead of from myth. Based on innovative critical analysis of both familiar and previously unexplored archival sources, and concentrating on accounts that can be attributed to the Besht or to contemporary eyewitnesses, this book goes further than any previous work in uncovering the historical Ba'al Shem Tov. Additionally, documents in Polish and Hebrew discovered by Professor Rosman during his research for the book enable him to give the first detailed description of the cultural, social, economic, and political context of the Besht's life."--
"Founder of Hasidism supplies the history behind the legend. It presents the best, most convincing description that can be drawn from the existing documentary evidence, changing our understanding of the Besht and with it the master-narrative of hasidism. A substantial new introduction considers what has changed in the study of Hasidism since the influential first edition was published, these changes being in part due to the effect of the book. New approaches, new sources, and new interpretations have been introduced, and these are reviewed and critically assessed. Criticisms of the original edition are answered and key issues reconsidered, including the authenticity of the various versions of the Holy Epistle; the ways in which Jacob Joseph of Polonne's books can be utilized as historical sources; and the relationship to history of the stories about the Ba'al Shem Tov in the hagiographical collection Shivhei Ha-Besht."--
Includes bibliographical references and index.
PDF (JSTOR, viewed June 18, 2018).
eBooks on EBSCOhost
Keywords: Baʻal Shem Ṭov, -- approximately 1700-1760.; Baʻal Shem Ṭov, -- approximately 1700-1760; Hasidim -- Ukraine -- Biography; Rabbis -- Ukraine -- Biography; Hasidism -- History -- 18th century; Rabbins -- Ukraine -- Biographies; Hassidisme -- Histoire -- 18e siècle.; RELIGION -- Judaism -- General; Hasidim; Hasidism; Rabbis; Ukraine; 1700-1799; Biography; Biographies; History; Biographies; Biographies